Tri Hita Karana Philosophy: From the Indigenous Religious Practice to Contemporary Educational Management - Nadeak, Bernadetha; Wiryadinata, Halim (Universitas Ahmad Dahlan, 2025)
This study examines how the philosophical Tri Hita Karana, as a Hindu religious value, has become the foundation of contemporary educational management in seeking the balance between social responsibility and community engagement. One of the purposes of education is to pursue social change in the community through social responsibility. However, cancerous capitalism distorts the meaning of education, leading educational capitalism to focus on economic matters. Therefore, the gap lies in how local culture serves as an inspiration for academic management. So, the Tri Hita Karana philosophy shapes educational management by emphasizing social responsibility and community engagement as the foundation of contemporary management axiology. The sociology of religion approach is applied through critical thinking by drawing on books, articles, journals, academic writings, and older manuscripts to develop an emic perspective. The result of this research is that the meaning of balance in life, which refers to the harmonious coexistence of economic, social, and cultural aspects, provides the foundation for educational management in seeking equilibrium between social responsibility and community engagement. This study concludes that Tri Hita Karana brings together management, education, and philosophy to reinforce one another.